THE INFLUENCE OF YOUTUBE LEARNING MEDIA ON THE UNDERSTANDING OF THE MATERIAL, THE SIZE OF CENTRAL SYMPTOMS AND THE RELIABILITY OF STATISTICS SUBJECTS FOR STUDENTS - Ina Marlina Lubis; Ambiyar; Mahesi Agni Zaus (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This research aims to (1) determine the feasibility of YouTube learning media on central symptom measurements and reliability. (2) Find out the effect of YouTube learning media on central symptom measurements and reliability. This research was conducted on students. The research method used was Research &; Development with the EDDIE development model. The results of this research: (1) Development of YouTube media on material measuring central symptoms and manufacturing reliability according to 3 material experts with an average of 95% in the category " Very worthy." Media expert validation was carried out on 2 experts and obtained an average result of 93% in the "Very worthy" category. an average of 95% in the "Very worthy" category. Media expert validation was carried out by 2 experts and obtained an average result of 93% in the "Very feasible" category. YouTube media in the material measuring central symptoms and reliability was declared suitable for use in teaching and learning activities based on the average value of the small group feasibility test with assessment scores. 82%, the medium group with an assessment score of 84%, and the feasibility test for the large group obtained an assessment score of 87% in the category "Very Feasible." (2). The influence of YouTube media on the material measuring central symptoms and reliability is stated to have a very big influence on students' understanding of learning material